Students’ Numeracy Literacy Skills Based on Severe Mathematics Anxiety and Gender-Role Attributes (Masculine/Feminine): A Qualitative Case Study - Aswan, Aswan; Pathuddin, Pathuddin; Ismaimuza, Dasa (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aims to describe in depth the students’ numeracy literacy abilities with severe mathematical anxiety from a masculine and feminine gender perspective. Severe mathematical anxiety can affect how students think, understand problems, and make decisions in solving mathematical problems. In addition, factors that influence mathematical performance are cognitive and affective patterns. Both of which are more related to gender-role than biological aspects (sex). This study considers gender perspectives, especially masculine and feminine, and it is expected to provide a more comprehensive picture of the diversity of students’ numeracy literacy abilities. This study used a qualitative approach with a case study type. The research subjects were selected through purposive sampling, utilizing a case study approach involving two individuals with severe levels of mathematics anxiety, specifically representing masculine (BM) and feminine (BF) gender characteristics. The data collection was carried out through questionnaires, numeracy literacy tests, and in-depth interviews. These data were analyzed using data condensation techniques, data display, and conclusion drawing. The case study results indicate that subjects BM and BF are capable of identifying essential information and understanding the problem context. However, there were differences in the stages of problem solving. BM tends to be able to evaluate the reasonableness of calculation results, while BF is better able to convey logical conclusions and relate the results to the problem context. This finding shows the importance of implementing learning strategies that accommodate differences in student characteristics to improve numeracy literacy skills in the aspect of using mathematical concepts, facts, and procedures.